EXTH-29. RADIOSENSITIZATION BY BRD4 INHIBITION IN DIFFUSE INTRINSIC PONTINE GLIOMA. (14th November 2022) - Watanabe, Jun; Clutter, Matt; Suri, Amreena; Abe, Koki; Ishi, Yukitomo; Becher, Oren; Hashizume, Rintaro
Abstract: Diffuse intrinsic pontine glioma (DIPG), the most frequent brainstem tumor in pediatrics, is one of the devastating childhood cancers, and virtually all patients die within two years after diagnosis. Since these tumors occur in the brainstem which is vital area, there are no surgical options for providing relief to patients, and conventional chemotherapy. Radiation therapy (RT) remains the only effective treatment. Radiosensitization is a mean to improve the therapeutic balance between efficacy and toxicity of RT, but not used in clinically. Here, we found BRD4 inhibitor as a radiosensitizer from drug screening. DIPG shows increased H3 K27 acetylation (H3K27ac), which binds to BET bromodomain protein 4 (BRD4) and they are strongly associated with active transcription. We tested two BRD4 inhibiter (BRD4i : AZD5153 and JQ-1) and genetic BRD4 depletion enhances radiation-induced DNA damage, making it a potential radiosensitizer in the treatment of DIPG. We evaluated the effects of BRD4i on genes expression using RNA sequence, inhibited significantly DNA-repair proteins such as BRCA1 and RAD51. CUT-RUN qPCR showed decreased H3K27ac at BRCA1 and RAD51. Combination with BRD4i and RT inhibited cell viability significantly in clonogenic survival assay, apoptosis assay, and showed cell cycle arrest. Radiation-induced DNA double-strand break (DSB) repair was prolonged high level of rH2AHX and 53BP1 with BRD4i because of inhibited DNA-repair. In vivo studies revealed increased survival of animals treated with combination therapy of RT and BRD4i in compared to either monotherapy. Together, these results highlight BRD4i as a potential radiosensitizer and provide a rationale for developing combination therapy with radiation in the treatment of DIPG.